The triple dividend of health: how SDG3 shapes human, economic, and environmental outcomes in EU - Alina Georgiana Manta; Roxana Maria Bădîrcea; Ramona Pîrvu; Riana Maria Ciobanu; Maria Nache Cimpoeru; Claudia Gherțescu (Journal of Business Economics and Management, 2026)
Achieving the Sustainable Development Goals (SDGs) requires understanding how progress in health and well-being (SDG3) impacts human development, economic performance, and environmental sustainability. This study analyses the effects of selected SDG3 indicators on Human Development Index (HDI), Gross Domestic Product (GDP per capita), and renewable energy usage across 27 EU countries (2014–2023), using three panel models with relevant control variables. Applying panel unit root, cointegration tests, and Fully Modified OLS (FMOLS) estimation, results show that better health and well-being significantly promote human development, economic output, and renewable energy adoption. In Model 1, life expectancy and well-being positively influence HDI, while fertility, neonatal mortality, and traffic deaths have negative effects; income inequality mildly reduces HDI. Model 2 finds that subjective well-being and lower tuberculosis incidence boost GDP, though health effects are smaller than on HDI. Model 3 links lower teen fertility and neonatal mortality to higher renewable energy use, suggesting synergy between health progress and clean energy transition. Overall, advancing SDG3 fosters human development, economic prosperity, and environmental sustainability, highlighting the need for integrated policies that simultaneously promote health, equality, education, and clean energy.